2019
DOI: 10.1590/2177-9465-ean-2018-0140
|View full text |Cite
|
Sign up to set email alerts
|

Health education practices of poisoning prevention for child in Family Health Strategy

Abstract: Objective: To analyze health education practices developed by health professionals of the Family Health Strategy team in the context of childhood poisoning. Method: Qualitative research, carried out during the months of July and August 2016, with 50 health professionals from nine Family Health Strategy teams of the city of Maringá-Paraná. Data were collected through semi-structured interviews and, subsequently, submitted to the thematic content analyses. Results: There were different perceptions and living exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
3
0
5
Order By: Relevance
“…The sociodemographic characteristics of the professionals interviewed influence the variables of the teaching-learning process in the context of child intoxication, considering the references used for this study (9) , since they integrate a team of professionals inserted in the community, who have established a bond with it throughout the years. To this end, it was found that these characteristics corroborate data on the composition of the Brazilian health workforce: most are female, young, with a higher educational level than required for their work, not to mention a high number of professionals with lato sensu postgraduation courses (3,19) .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The sociodemographic characteristics of the professionals interviewed influence the variables of the teaching-learning process in the context of child intoxication, considering the references used for this study (9) , since they integrate a team of professionals inserted in the community, who have established a bond with it throughout the years. To this end, it was found that these characteristics corroborate data on the composition of the Brazilian health workforce: most are female, young, with a higher educational level than required for their work, not to mention a high number of professionals with lato sensu postgraduation courses (3,19) .…”
Section: Discussionsupporting
confidence: 63%
“…The home can be especially unsafe for children, since it contains objects and materials that offer risk in all of its rooms. This is especially true with regard to the diversity of chemical products, which favor intoxication and are mostly stored in places that the child can easily access (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study conducted in 2016 with 50 healthcare professionals from the Family Health Program showed that educational practices related to childhood poisoning promoted by these agents were mainly focused on first aids concepts, with little discussion on actual poisoning accident prevention strategies. 29 If adopted by the Family Health Program agents, directed poisoning prevention education to parents -including increasing knowledge of poisons and poisoning prevention behaviors such as safe storage of medications and cleaning products -could possibly reduce childhood poisoning rates. 24 Prevention with education improves poisoning prevention practices and encourages the need of legislative measures, such as those related to childproof bottles.…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded, therefore, that interventions in HP are an integrating path of care and are based on technical, scientific, and cultural knowledge, and have the capacity to produce individual and family changes. As HE is linked to HP, it is assumed that the family is empowered with autonomy and not just with disease prevention attitudes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%